The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.5812/hepatmon.24449
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Platelet Count as a Noninvasive Marker and Ultrasonographic Grading in Patients With Nonalcoholic Fatty Liver Disease

Abstract: Background:Nonalcoholic fatty liver disease has become a worldwide challenge. Liver biopsy remains the single most reliable approach to determine the severity of this disease. As patients with nonalcoholic fatty liver disease require close follow-up, performing this invasive method repeatedly seems impractical; therefore, designing a noninvasive system to follow up patients has become a common interest.Objectives:We intended to investigate the association between platelet counts of patients with nonalcoholic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 38 publications
(49 reference statements)
1
24
2
Order By: Relevance
“…In animal studies, a high-fat diet induced NASH mouse model exhibited elevated PIIINP [24]and Hamza et al also reported that mean serum levels of PIIINP in children with NAFLD (assessed by ultrasonography) were higher than those in control children [25].Our results are consistent with previous studies and Elevated serum PIIINP has been previously been shown to be associated with elevated pro-inflammatory cytokines in liver disease [9].PLTs have a role in thrombosis formation and evidence pointing to association between PLT count and liver injury [26]. In a study, it was reported that patients with moderate-to-severe NAFLD had higher PLT counts than milder form of NAFLD [27]and PLT count has been included in some scoring systems such as NAFLD fibrosis score [28]. In addition, platelets play a pivotal role in both hepatic regeneration and fibrosis pathophysiology and Platelets contain HGF [29],Our study also found that both PLT and HGF in NAFLD increased with the increase in severity of NAFLD, which may be the protective mechanism of the liver in the inflammatory state.…”
Section: Discussionsupporting
confidence: 90%
“…In animal studies, a high-fat diet induced NASH mouse model exhibited elevated PIIINP [24]and Hamza et al also reported that mean serum levels of PIIINP in children with NAFLD (assessed by ultrasonography) were higher than those in control children [25].Our results are consistent with previous studies and Elevated serum PIIINP has been previously been shown to be associated with elevated pro-inflammatory cytokines in liver disease [9].PLTs have a role in thrombosis formation and evidence pointing to association between PLT count and liver injury [26]. In a study, it was reported that patients with moderate-to-severe NAFLD had higher PLT counts than milder form of NAFLD [27]and PLT count has been included in some scoring systems such as NAFLD fibrosis score [28]. In addition, platelets play a pivotal role in both hepatic regeneration and fibrosis pathophysiology and Platelets contain HGF [29],Our study also found that both PLT and HGF in NAFLD increased with the increase in severity of NAFLD, which may be the protective mechanism of the liver in the inflammatory state.…”
Section: Discussionsupporting
confidence: 90%
“…Platelet count has been shown to be a valuable surrogate biomarker predicting the severity of fibrosis in NAFLD patients [39] and could be used to predict the activity of the disease [40]. …”
Section: Discussionmentioning
confidence: 99%
“…The results from a Japanese study suggested that the platelet counts could be served as an ideal biomarker of the severity of fibrosis in NAFLD patients [ 8 ]. However, a more recent study in Iran reported that NAFLD has nothing to do with peripheral platelet counts [ 9 ].…”
Section: Introductionmentioning
confidence: 99%